1998
DOI: 10.5144/0256-4947.1998.176
|View full text |Cite
|
Sign up to set email alerts
|

Blood Stream Infections: Micro-Organisms, Risk Factors and Mortality Rate in Qatif Central Hospital

Abstract: Blood stream infections (BSI) lead to sepsis and septic shock, which continue to be important causes of morbidity and mortality. A vast body of literature has been devoted to this. Worldwide studies about the epidemiology, microbiological etiology and prognosis of BSI have been performed over the last six decades. These have shown changing patterns of the pathogens involved, namely the emergence of gram-negative pathogens as a major cause of bacteremia after the beginning of the antimicrobial era, 1,2 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
4
14
1
Order By: Relevance
“…This finding has been observed by other recent Indian studies 2015 by Shweta Bohra et al 8 and 2011 by Vanita Rani et al 9 These authors have also noted E. coli and Klebsiella pneumoniae as predominant gram-negative bacteria causing sepsis. However, this finding is not matching with that of studies in USA 10 15,16,17 The possible explanation for the difference could be the difference in blood culture system, the study design, geographical location, nature of patient population, epidemiological difference of the aetiological agents and seasonal variation. 18,19 Amongst the gram-positive bacteria staphylococci (33.3%), coagulase negative staphylococci (29.3%) and enterococci (26.5%) were predominant aetiological agents in our study.…”
Section: Discussioncontrasting
confidence: 74%
“…This finding has been observed by other recent Indian studies 2015 by Shweta Bohra et al 8 and 2011 by Vanita Rani et al 9 These authors have also noted E. coli and Klebsiella pneumoniae as predominant gram-negative bacteria causing sepsis. However, this finding is not matching with that of studies in USA 10 15,16,17 The possible explanation for the difference could be the difference in blood culture system, the study design, geographical location, nature of patient population, epidemiological difference of the aetiological agents and seasonal variation. 18,19 Amongst the gram-positive bacteria staphylococci (33.3%), coagulase negative staphylococci (29.3%) and enterococci (26.5%) were predominant aetiological agents in our study.…”
Section: Discussioncontrasting
confidence: 74%
“…were the nine most common noteworthy bacterial pathogens causing BSI. More or less similar observations have been made in cases of bacteraemia in different countries, however, the proportion and predominance of the organisms varied [5,12,18,19,22,24]. …”
Section: Discussionmentioning
confidence: 77%
“…Several studies in different countries, Jimma Ethiopia, (60.9% and 39.1%) Gondar Ethiopia (70.2% and 29.8%), Zimbabwe (71.9% and 28.1%) Addis Ababa Ethiopia (62.6% and 37.4%), have shown marginally higher prevalence of Gram-positive and lower prevalence of Gram-negative organisms, respectively [12,18,19,21]. On the contrary, Gram-negative bacteria have been reported as the commonest cause of bacteremia in hospitalized febrile patients in developing countries in studies conducted in Nigeria (69.3% and 30.7%), Saudi Arabia (62.2% and 33.8%), Tanzania (69.7%, 30.3%) [17,22,23]. The possible explanation for the difference could be the difference in blood culture system, the study design, geographical location, nature of patient population, epidemiological difference of the etiological agents, and seasonal variation.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively higher rates (521 microbial isolates, 63%) were observed for the overall HA BSIs than the CA. The varying HA BSI rates (90% (Al-Tawfiq and Abed, 2009); 43% (Elbashier et al, 1998); 53% (Laupland et al, 2009) have been reported earlier.…”
Section: Most Common Pathogens Isolatedmentioning
confidence: 56%